2000
DOI: 10.1182/blood.v96.12.3719.h8003719_3719_3724
|View full text |Cite
|
Sign up to set email alerts
|

An open-label study of the role of adjuvant hemostatic support with protein C replacement therapy in purpura fulminans–associated meningococcemia

Abstract: Activated protein C (APC) is a natural anticoagulant that plays a pivotal role in coagulation homeostasis. Severe inherited or acquired deficiency results in a clinical syndrome called purpura fulminans. In addition, APC also appears to have potent cytokine-modifying properties and is protective in animal models of sepsis. The dual functional properties of APC are particularly relevant to severe meningococcemia, where acquired PC deficiency is accompanied by multiorgan failure and purpura fulminans. The author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Clinical observations indicate that the degree of protein C reduction correlates with a negative prognosis in septic patients (Fisher & Yan, 2000). Indeed, protein C supplementation has been found to decrease purpura fulminans (Rivard et al, 1995) in patients with meningococcemia and apparently to increase survival (White et al, 2000a). The impact on the superficial thrombotic lesions is quite consistent with the demonstrated ability of protein C supplementation to reverse the purpura fulminans that develops in patients with severe protein C deficiency (Dreyfus et al, 1991).…”
Section: The Impact Of Inflammation On Coagulationmentioning
confidence: 65%
“…Clinical observations indicate that the degree of protein C reduction correlates with a negative prognosis in septic patients (Fisher & Yan, 2000). Indeed, protein C supplementation has been found to decrease purpura fulminans (Rivard et al, 1995) in patients with meningococcemia and apparently to increase survival (White et al, 2000a). The impact on the superficial thrombotic lesions is quite consistent with the demonstrated ability of protein C supplementation to reverse the purpura fulminans that develops in patients with severe protein C deficiency (Dreyfus et al, 1991).…”
Section: The Impact Of Inflammation On Coagulationmentioning
confidence: 65%
“…In contrast, non-activated plasma-derived human protein concentrate (hPC) has been successfully used in paediatric, neonatal and adult patients at high-risk of haemorrhage, especially in those suffering from meningococcal septic shock (7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Over the past decade, a number of case reports and one small series has suggested that PC replacement therapy is associated with a reduction in morbidity and mortality in patients with severe meningococcaemia and purpura fulminans (Rivard et al, 1995;Smith et al, 1997;Rintala et al, 1998;Smith & White, 1999). In the past year, further evidence to support the dual functional property (anticoagulant and anti-inflammatory) of PC/APC has emerged from two published clinical studies (White et al, 2000a;Bernard et al, 2001). The first was an open-label prospective study assessing the efficacy of PC replacement therapy in patients with severe meningococcal septicaemia, purpura fulminans and multiorgan failure, and its use was associated with a significant reduction in predicted morbidity and mortality (White et al, 2000a).…”
mentioning
confidence: 99%
“…In the past year, further evidence to support the dual functional property (anticoagulant and anti-inflammatory) of PC/APC has emerged from two published clinical studies (White et al, 2000a;Bernard et al, 2001). The first was an open-label prospective study assessing the efficacy of PC replacement therapy in patients with severe meningococcal septicaemia, purpura fulminans and multiorgan failure, and its use was associated with a significant reduction in predicted morbidity and mortality (White et al, 2000a). The second was the first randomized trial to use this anticoagulant in patients with severe sepsis and again the study showed a significant reduction in mortality associated with the use of APC despite an increase in haemorrhagic events (Bernard et al, 2001).…”
mentioning
confidence: 99%